Burden of illness associated with pneumococcal infections in Japan - a targeted literature review - Ataru Igarashi; Maki Ueyama; Koki Idehara; Mariko Nomoto (Taylor & Francis Group, 2022)
Introduction: Pneumococcal diseases (PDs) are among the leading causes of mortality and morbidity worldwide. However, the evidence on epidemiology, health economic, and patient-reported outcomes has not been systematically reviewed and published in Japan. This study aimed to assess the burden, treatment adherence and compliance, and serotype distribution associated with PDs in Japan. Method: One hundred and eight studies were identified between January 2005 and June 2020. The identified studies were mostly regional and with a limited scale, clinical settings, and populations. Results: In 2013-2017, invasive PD incidence rates were 4.98-9.47/100,000 in <4-year-olds, 0.36/100,000 in 5-14-year-olds, 0.46/100,000 in 15-64-year-olds, and 1.50-5.38/100,000 in the elderly. The incidence of invasive PDs in children decreased from 24.6/100,000 in 2008 to 10.7/100,000 in 2013 after the introduction of PCV7 and further declined to 10.3/100,000 in 2014 after PCV13 was introduced. From 2014, the prevalence of PCV13 serotypes decreased across all age groups along with a decrease of PPV23 serotypes, but an increase of PPV23 serotypes not included in PCV13 among adults and the elderly. No study reported health-related quality-of-life data for PDs. In children, direct costs were 340,905-405,978 JPY (3,099-3,691 USD) per pneumococcal bacteraemia, 767,447-848,255 JPY (6,977-7,711 USD) per pneumococcal meningitis, and 79,000 JPY (718 USD) per pneumococcal acute otitis media episodes. In adults and the elderly, the direct cost of pneumococcal pneumonia was 348,280-389,630 JPY (3,166-3,542 USD). The average hospital stay length was 7.2-31.9 days in children, 9.0 days in adults and 9.0-28.7 days in adults and the elderly. Conclusions: The epidemiological burden of PDs remains high in Japan, especially among children and the elderly with invasive PDs accounting for a very small proportion of all PDs. A significant impact of the PCV13 vaccine program was reported, while the PPV23's impact remains unclear. A substantial decrease in quality-adjusted life years in adults and the elderly and a high economic burden may exist.